(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: Securing sensitive data in multi-cloud environments poses significant challenges. This paper presents an Enhanced Product Cipher-Based Distributed Steganography (E-PCDS) mechanism designed to elevate data security. Building upon traditional PCDS, E-PCDS introduces advanced security layers, dynamic adaptability, and efficiency improvements. The method uses unaltered cover media for data fragmentation and concealment, dynamically distributing hidden data across multiple cloud platforms to minimize detection risks. Key enhancements include a dynamic key exchange via Diffie-Hellman, rotating base values, multi-layered permutations, randomized file allocation, and context-aware decoding. These innovations ensure robust, undetectable data hiding and retrieval, significantly increasing resistance to unauthorized access and brute-force attacks. Comprehensive security analysis demonstrates the method's resilience, making data extraction computationally infeasible even with full access to all cloud accounts. E-PCDS sets a new standard in cloud security and steganography, providing a highly secure solution for data concealment in multi-cloud environments.